Effectiveness of Infliximab and Interferon Alpha-2a for the Treatment of Behçet's Uveitis: Customizing Therapy according to the Clinical Features. (17th February 2022) - De Simone, Luca; Invernizzi, Alessandro; Aldigeri, Raffaella; Mastrofilippo, Valentina; Marvisi, Chiara; Gozzi, Fabrizio; Bolletta, Elena; Adani, Chantal; Pipitone, Nicolò; Muratore, Francesco; Fontana, Luigi; Salvarani, Carlo; et al.
ABSTRACT: Purpose: To report long term results of biologic treatment of severe and refractory Behçet's uveitis (BU) choosing a different biologic agent according to the uveitis clinical features. Methods: Retrospective cohort of patients with BU refractory to conventional therapy, who received Interferon (IFN) alpha-2a or Infliximab (IFX) for at least 3 months. Results: Twenty-two patients were included (mean age 29 ± 10 years, 63% males); Fifteen received IFN and 7 IFX, for a mean treatment period of 30 ± 24(SD) months. Twenty (90%) patients discontinued treatment, in most cases for complete remission (77%). Seven patients (32%) showed relapses during treatment and five (23%) after discontinuation. Visual acuity improved significantly in IFN group and all eyes showed a significant decrease in central macular thickness at 12 months. Conclusions: Both IFX and IFN Alpha-2a were effective and well tolerated in the treatment of refractory BU using a customized approach based on the uveitis features.